Hubungan kepuasan kerja dengan keberkesanan secara kolektif dan kesejahteraan hidup dalam kalangan pensyarah di Institut Pendidikan Guru Kampus Gaya Kota Kinabalu Sabah - Ain Apainah, Yuni (2010)
The main purpose of this research is to analyze the job satisfaction level in relation to the collective effectiveness and harmonious life of lecturers in IPG Gaya Kota Kinabalu, Sabah. The research involved 80 lecturers of IPG Gaya as respondents. The research involved survey through the use of questionnaires. Analysis of data was conducted through the use of descriptive statistic and infancy such as to find the frequency. percentage, mean, T-test ANOVA One way test and Pearson. T- test was use to find out the differences of the level of lecturers satisfaction mean based on gender. ANOVA one way test was used to find out the differences of job satisfaction mean of lecturers based on marital status, education level, teaching experience, subject taught and monthly income. Pearson correlation was used to determine the strength of relations of the variables analyzed. The findings reveals that job satisfaction level and lecturers effectiveness are average while harmonious life is at a high level. T-test shows there is no significant difference in job satisfaction based on gender. ANOVA shows that there is no significant difference in job satisfaction based on marital status. education level, teaching experience and subject taught. Sob satisfaction ANOVA based on monthly income shows significant difference and pos hoc shows that the group with the monthly income of RM3500-3599 with RM5000 above are significant different. Pearson correlation test shows there is a positive relationship with effectiveness ( r = .661) and job satisfaction with harmonious life ( r = .778)